The Impact of Dam Reservoir on Flood Reduction (Case Study Logung Reservoir, Kudus, Central Java) - Fajriani, Qonaah Rizqi; Nur Utari, Khoirunnisa Ulya; Nurulita, Ria (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
The Indonesian government targeted building 65 reservoirs and dams in 2015-2022. The purpose is to maintain food security facing the long-term climate crisis, besides reducing the impact of a flood. Logung Reservoir is located on the Logung River, Kudus, Central Java. This earth-fill dam was built to solve the flood and drought problems in Kudus. However, the existence of the Logung Reservoir gives a risk to the downsteam area. The purpose of this research is to study flood reduction and the risk of overtopping, which can cause a dam break, and to calculate the Logung Reservoir spillway’s performance in handling floods. This study is based on four main steps: the rainfal-runoff modelling, the extreme rainfall estimation, the hydrograph inflow of the dam estimation, and the evaluation of food reduction. The results of the 1000-year rainfall analysis and PMP for the Logung dam basin were 409 mm and 704 mm, respectively. Rainfall distribution is made using ABM, and effective rainfall is calculated by the SCS method. Land use analysis in the Logung dam watershed obtained a CN-II of 71.4 and a CN-III of 85.2. The rainfall-runoff transformation method used a unit hydrograph. The Nakayasu and Gama-I unit hydrographs show significant differences from the peak discharge, although not for the time base. The flood hydrograph design affects the reservoir performance. The reservoir flood routing results a dumping efficiency of 35% for the 1000-year and 21% for PMF. The 1000-year flood routing shows that there was no risk of overtopping. The highest water level on the PMF flood routing at +94.1. Several solutions can prevent overtopping by reducing inflow discharge through small dams upstream, increasing the green area, or modifying spillway structure.